Community treatment of drug misuse : more than methadone - Seivewright, Nicholas (Studies in social and community psychiatry., 2000)
"Does the widespread use of methadone achieve the right balance between treatment of the individual and management of a public health problem?" "This book draws on the author's direct clinical experience and makes use of findings from Europe, North America and Australia to provide a comprehensive and detailed guide to service provision and treatment for drug misuse, including methadone and alternative opiate substitutes, detoxification methods, naftrexone and relapse prevention, and possible approaches with nonopiate users."--Jacket